Análisis y caracterización de los sitios de diversión nocturna ante la propuesta para la creación de una Zona Rosa en la ciudad de Loja, periodo 2013 - Valdiviezo Iñiguez, Jennypher Viviana (2016)
In the city of Loja, a latent problem of social and public nature that generates various criteria of the community is the dispersion of nightlife sites, because they are in different residential areas of our city; consequently, discomfort that affect those who live around the sites nightlife, as concern about the presence of libadores in the streets, squares parks and other public places, cause, street scandals, fights, noise, which often attracts the presence of miscreants who take advantage of these excesses to commit robberies and assaults, generating insecurity, affecting passers-by and residents of the sector. This violates the right to rest and leisure, of whom reside around these places of entertainment, and, additionally, the bad image of the city opposite the tourism, since the disorder and scattering of bars and nightclubs is evident for the above should be considered to the present investigation. To know the reality of this problem from a public perspective, he resorted to methods: synthetic, descriptive, deductive analytical and application of the techniques and the survey of the inhabitants of the towns of San Sebastian, Cdla. Zamora, La Algeria, bus terminal and Western Pass. He also met the Director of the Department of Forecasting and Projects Municipal GAD Loja.; Commander Distr. 1 of the National Police; Chief of Police and Chief Councillor GAD Loja, determining the importance of a public policy to combat relocation problem. 6 The main data obtained in the results, announced that 64% of the population living near these areas have been victims of crime, 62% every week takes complaints about noise and disorderly generated a 45% feel affected in declining health for insomnia, auditory and others; and 99% of the population said that these establishments must relocate. On the other side of the coin, only 35% of the owners of nightclubs access to relocation, but not before they have shown stress that there should be the necessary facilities, such as having access to public services, and financial aid for that Instead, requesting exemptions items concerning tax liability. As the main objective of the research has raised a proposed municipal ordinance on the use of public spaces and the relocation of these sites nightlife in one place called Zona Rosa, it will allow providing security to the citizens, as It turns the competent authorities may carry out their control tasks in an organized and efficient way.